Ulama Pasca Sunan Gunung Jati: Jaringan Intelektual Islam Cirebon Abad ke-16 sampai dengan Abad ke-18 - Rosidin, Didin Nurul (JSW (Jurnal Sosiologi Walisongo), 2017)
This article related to the dynamic of islam intellectual network in Cirebon post Sunan Gunung Jati in the late of 16 century until early of 18 century. This era has been crucial because every dynamic of islam intellectual network happened after the death of Sunan Gunung Jati. Then the implication had headed to the existence of islamic education institution which is held in Keraton, one of the basis where islamic intellectual network in Cirebon, and also to the dominant intellectual discourse that evolved for two centuries. There are three stages of islam intellectual network progress in Indonesia which is related to middle east as a center and also main reference since 13 century untill 20 century. Firts, islamisasi (islamisation). This was when Islam for the first time spreaded by moslemâ€™s traders, travelers, and moslem scholars (ulama). This happened around 13 century. Second, neo-sufism. Neo sufism has occured for 3 centuries, since 16 centuries till 18 centuries. In this era some moslem scholars have had significant roles to disseminate knowledge and movement from middle east to Nusantara. And third, purification of islam. Some moslem scholars that have already finished their study and hajj became active to spread the ideas of purification of islam which developed in middle east.Â Â